Association of psychosocial factors with all‐cause hospitalizations in patients with atrial fibrillation. Issue 1 (10th November 2020) - Meyre, Pascal B.; Springer, Anne; Aeschbacher, Stefanie; Blum, Steffen; Rodondi, Nicolas; Beer, Juerg H.; Di Valentino, Marcello; Ammann, Peter; Blum, Manuel; Mathys, Rebecca; Meyer‐Zürn, Christine; Bonati, Leo H.; et al.
Abstract: Background: A high burden of cardiovascular comorbidities puts patients with atrial fibrillation (AF) at high risk for hospitalizations, but the role of other factors is less clear. Hypothesis: To determine the relationship between psychosocial factors and the risk of unplanned hospitalizations in AF patients. Methods: Prospective observational cohort study of 2378 patients aged 65 or older with previously diagnosed AF across 14 centers in Switzerland. Marital status and education level were defined as social factors, depression and health perception were psychological components. The pre‐defined outcome was unplanned all‐cause hospitalization. Results: During a median follow‐up of 2.0 years, a total of 1713 hospitalizations occurred in 37% of patients. Compared to patients who were married, adjusted rate ratios (aRR) for all‐cause hospitalizations were 1.28 (95% confidence interval [CI], 0.97‐1.69) for singles, 1.31 (95%CI, 1.06‐1.62) for divorced patients, and 1.02 (95%CI, 0.82‐1.25) for widowed patients. The aRRs for all‐cause hospitalizations across increasing quartiles of health perception were 1.0 (highest health perception), 1.15 (95%CI, 0.84‐1.59), 1.25 (95%CI, 1.03‐1.53), and 1.66 (95%CI, 1.34‐2.07). No different hospitalization rates were observed in patients with a secondary or primary or less education as compared to patients with a college degree (aRR, 1.06; 95%CI, 0.91‐1.23 and 1.05; 95%CI, 0.83‐1.33, respectively). Presence of depression was not associated with higher hospitalization rates (aRR, 0.94; 95%CI, 0.68‐1.29). Conclusions: The findings suggest that psychosocial factors, including marital status and health perception, are strongly associated with the occurrence of hospitalizations in AF patients. Targeted psychosocial support interventions may help to avoid unnecessary hospitalizations. Trial registration: ClinicalTrials.gov Identifier NCT02105844.